7x+5(2x-3)=9-7x

Simple and best practice solution for 7x+5(2x-3)=9-7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+5(2x-3)=9-7x equation:


Simplifying
7x + 5(2x + -3) = 9 + -7x

Reorder the terms:
7x + 5(-3 + 2x) = 9 + -7x
7x + (-3 * 5 + 2x * 5) = 9 + -7x
7x + (-15 + 10x) = 9 + -7x

Reorder the terms:
-15 + 7x + 10x = 9 + -7x

Combine like terms: 7x + 10x = 17x
-15 + 17x = 9 + -7x

Solving
-15 + 17x = 9 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
-15 + 17x + 7x = 9 + -7x + 7x

Combine like terms: 17x + 7x = 24x
-15 + 24x = 9 + -7x + 7x

Combine like terms: -7x + 7x = 0
-15 + 24x = 9 + 0
-15 + 24x = 9

Add '15' to each side of the equation.
-15 + 15 + 24x = 9 + 15

Combine like terms: -15 + 15 = 0
0 + 24x = 9 + 15
24x = 9 + 15

Combine like terms: 9 + 15 = 24
24x = 24

Divide each side by '24'.
x = 1

Simplifying
x = 1

See similar equations:

| .02z=z | | h(t)=-t^2+20t | | y^3=x+13 | | -.75z+.125=-.125-.08 | | 15.5=7v | | y=(4x^2+3)(5x^4-11) | | 8x+10-2x=13-14x-15 | | -4+n*2=0 | | Y-10=4(x-4) | | 10.1x+3.6=123.8 | | .17z+.5=-.5z-1 | | =16.25 | | y=(25x-3)(x^2-11) | | -4+n*2=12 | | -3x-2(9+5x)=17-2(2x-2) | | 4x-29=4x+2 | | 8x^2-3x-6=0 | | 2v+5=2v-4 | | -0.7x+0.5=-0.9-1.1x | | .15x+0.4(x-5)=.01(3x-3) | | 56p^7q+21p^6q^3+49p^4q^2=7p^4q | | -4x^2-31x-21=0 | | .67z-2.01=-.8z-2.4 | | 1.1+19.5=43.7 | | 4x+5+2x+3+20=180 | | 12x+6x+90=180 | | Y=5sin(2x) | | x-16/2=-1 | | 96=56+f | | 3.9/5.4=x/8.1 | | 2/3z | | 20y+39=4y+7 |

Equations solver categories